2016
DOI: 10.4081/ija.2016.725
|View full text |Cite
|
Sign up to set email alerts
|

Engineered nanomaterials and crops: physiology and growth of barley as affected by nanoscale cerium oxide

Abstract: In recent years, remarkable progress has been made in developing nanotechnology. This has led to a fast-growth of commercial applications, which involve the use of a great variety of manufactured nanomaterials. Given that, soils and sediments are the ultimate sinks of engineered nanomaterials (ENMs), they can be taken up by microorganisms, nematodes, earthworms or plants, and potentially transferred to the food chain up to animals and humans. However, the reactions of the biota exposed to ENMs of different siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The following studies come into disagreement since in the first case cerium caused phytotoxicity while in the second one, it reported many improvements. A study conducted in the Mediterranean region showed unexpected results: in a seed trial CeO2 reduces total root length while in barley (Hordeum vulgare) life cycle study negatively affects potassium and sulfur uptake (Mattiello et al, 2016). On the other hand, another experiment performed by Rico et al (2014) on wheat (T. aestivum) reported that CeO2 can improve plant growth, shoot biomass, and grain yield.…”
Section: Nanoparticles As Nano-fertilizers and Biofortificatorsmentioning
confidence: 99%
“…The following studies come into disagreement since in the first case cerium caused phytotoxicity while in the second one, it reported many improvements. A study conducted in the Mediterranean region showed unexpected results: in a seed trial CeO2 reduces total root length while in barley (Hordeum vulgare) life cycle study negatively affects potassium and sulfur uptake (Mattiello et al, 2016). On the other hand, another experiment performed by Rico et al (2014) on wheat (T. aestivum) reported that CeO2 can improve plant growth, shoot biomass, and grain yield.…”
Section: Nanoparticles As Nano-fertilizers and Biofortificatorsmentioning
confidence: 99%